Correlated Magnetic Weyl Semimetal State in Strained Pr2Ir2O7. Issue 25 (14th May 2021) - Li, Yangyang; Oh, Taekoo; Son, Jaeseok; Song, Jeongkeun; Kim, Mi Kyung; Song, Dongjun; Kim, Sukhyun; Chang, Seo Hyoung; Kim, Changyoung; Yang, Bohm‐Jung; Noh, Tae Won
Abstract: Correlated topological phases (CTPs) with interplay between topology and electronic correlations have attracted tremendous interest in condensed matter physics. Therein, correlated Weyl semimetals (WSMs) are rare in nature and, thus, have so far been less investigated experimentally. In particular, the experimental realization of the interacting WSM state with logarithmic Fermi velocity renormalization has not been achieved yet. Here, experimental evidence of a correlated magnetic WSM state with logarithmic renormalization in strained pyrochlore iridate Pr2 Ir2 O7 (PIO) which is a paramagnetic Luttinger semimetal in bulk, is reported. Benefitting from epitaxial strain, "bulk‐absent" all‐in–all‐out antiferromagnetic ordering can be stabilized in PIO film, which breaks time‐reversal symmetry and leads to a magnetic WSM state. With further analysis of the experimental data and renormalization group calculations, an interacting Weyl liquid state with logarithmically renormalized Fermi velocity, similar to that in graphene, is found, dressed by long‐range Coulomb interactions. This work highlights the interplay of strain, magnetism, and topology with electronic correlations, and paves the way for strain‐engineering of CTPs in pyrochlore iridates. Abstract : A novel correlated magnetic Weyl semimetal state with logarithmic renormalization is experimentally realized in the high‐quality strained film of Pr2 Ir2 O7 . Strain‐induced all‐in–all‐out antiferromagnetic ordering breaks time‐reversal symmetry and leads to the magnetic Weyl semimetal state. Combing the experimental results and renormalization group calculations, an interacting Weyl semimetal state with logarithmic Fermi velocity renormalization is reported, dressed by long‐range Coulomb interactions.